Experimental evidence and molecular modeling of the interaction between hRSV-NS1 and quercetin - Gomes, Deriane Elias [UNESP]; Caruso, Ícaro Putinhon [UNESP]; de Araujo, Gabriela Campos [UNESP]; de Lourenço, Isabella Otenio [UNESP]; de Melo, Fernando Alves [UNESP]; Cornélio, Marinônio Lopes [UNESP]; Fossey, Marcelo Andrés [UNESP]; de Souza, Fátima Pereira [UNESP] (Elsevier, 2016)
Human Respiratory Syncytial Virus is one of the major causes of acute respiratory infections in children, causing bronchiolitis and pneumonia. Non-Structural Protein 1 (NS1) is involved in immune system evasion, a process that contributes to the success of hRSV replication. This protein can act by inhibiting or neutralizing several steps of interferon pathway, as well as by silencing the hRSV ribonucleoproteic complex. There is evidence that quercetin can reduce the infection and/or replication of several viruses, including RSV. The aims of this study include the expression and purification of the NS1 protein besides experimental and computational assays of the NS1-quercetin interaction. CD analysis showed that NS1 secondary structure composition is 30% alpha-helix, 21% beta-sheet, 23% turn and 26% random coils. The melting temperature obtained through DSC analysis was around 56°C. FRET analysis showed a distance of approximately 19Å between the NS1 and quercetin. Fluorescence titration results showed that the dissociation constant of the NS1-quercetin interaction was around 10-6M. In thermodynamic analysis, the enthalpy and entropy balanced forces indicated that the NS1-quercetin interaction presented both hydrophobic and electrostatic contributions. The computational results from the molecular modeling for NS1 structure and molecular docking regarding its interaction with quercetin corroborate the experimental data.
Keywords: Flavonoids; Fluorescence spectroscopy; Human syncytial respiratory virus; Molecular modeling; Non structural protein 1; Quercetin